Birds of Lake Jempang and the middle Mahakam wetlands, East Kalimantan - Christian Gonner (KUKILA, 2000)
Between 1988 and 1999 avifaunistic data were collected in the wetlands around Danau Jempang (Kutai, East Kalimantan) over a period of 40 months. A total of 90 bird species was found, including important breeding populations of various herons and the Lesser Adjutant Leptoptilos javanicus. Breeding was also noted for the Little Tern Sterna albifrons, which appears to be the first breeding record for Borneo. The bird communities of 6 habitat types are discussed and compared with other wetland areas in Kalimantan. Repeated forest fires, extensive land conversion plans, and the catching of herons and storks, indicate the need for an immediate conservation plan for one of Kalimantan's most important wetland sites and its avifauna. Some recommendations towards such a plan are given.